Civil Islam : Muslims and democratization in Indonesia - Hefner, Robert W., 1952- (Princeton studies in Muslim politics., 2000)
"Civil Islam" tells the story of Islam and democratization in Indonesia, the world's largest Muslim nation. Challenging stereotypes of Islam as antagonistic to democracy, this study of courage and reformation in the face of state terror suggests possibilities for democracy in the Muslim world and beyond. Democratic in the early 1950s and with rich precedents for tolerance and civility, Indonesia succumbed to violence. In 1965, Muslim parties were drawn into the slaughter of half a million communists. In the aftermath of this bloodshed, a "New Order" regime came to power, suppressing democratic forces and instituting dictatorial controls that held for decades. Yet from this maelstrom of violence, repressed by the state and denounced by conservative Muslims, an Islamic democracy movement emerged, strengthened, and played a central role in the 1998 overthrow of the Soeharto regime. In 1999, Muslim leader Abdurrahman Wahid was elected President of a reformist, civilian government. In explaining how this achievement was possible, Robert Hefner emphasizes the importance of civil institutions and public civility, but argues that neither.